Strategi Adaptasi Keuangan UMKM dalam Menghadapi Persaingan Global di Kota Makassar - Nurhaedah (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2025)
This research aims to analyze the financial adaptation strategies implemented by UMKM in Makassar City in facing global competition. In global competition, UMKM need to have strong competitive advantages, including financial management. Financial Technology (Fintech) can be a tool that supports MSME business growth, especially in the financing aspect. It is important to increase financial literacy along with the use of fintech, so that UMKM players can be wiser in choosing and using sources of financial access for the progress of their business. With a good understanding of financial literacy, it is hoped that UMKM will be able to utilize and manage existing financial resources more effectively. The method used in this paper is descriptive qualitative analysis and literature study, which aims to explain the application of Financial Technology (Fintech). The research results show that UMKM implement various financial adjustment strategies by considering factors such as business characteristics, external environment, and state support which also influence UMKM' financial adjustment strategies. This study has a significant impact on UMKM, the government, and related parties to increase the competitiveness of UMKM that have implemented several financial adjustment strategies, including better cash flow management, use of financial technology (Fintech), product diversification, and increased funding. Apart from that, internal factors such as management knowledge and external factors such as government support also influence the success of adaptation strategies. Overall, this adaptation strategy has proven effective in increasing the competitiveness of UMKM in the global market.